On a Potential Paradox of a Public Service Internet - Elisabeth Korn; Jens Schröter (tripleC: Communication, Capitalism & Critique)
Digital capitalism undermines deliberative democracy. This is the diagnosis arrived at by The Public Service Media and Public Service Internet Manifesto (2021), edited by Christian Fuchs and Klaus Unterberger, and Jürgen Habermas’ A New Structural Transformation of the Public Sphere and Deliberative Politics (2023). They condemn the commercial Internet as a deformation of the public sphere and conclude that it needs to be fundamentally restructured. Interestingly, both texts propose to restructure it after the template of broadcasting media. We seek to challenge this approach from a media-political perspective, arguing that it revives an elapsed version of democracy by rekindling the mass media paradigm to which it was bound. Both texts are implicitly based on the assumption that a technology that emerged in capitalism can be used for different, even contradictory, purposes. But what if the media structure of digital communication, irrespective of who owns or controls it, denies its democratic instrumentalisation?